Rope climbing robot - Noor Juraizah, Mohd Jinal (2009)
The objective of this project is to build a hardware and software of a Rope Climbing Robot and to-study the motion of a robot that can climb rope. The robot can climb up via the rope. The robot weight must be not too heavy because it has to climb up via a rope to get the target. The research of the project has been done using a Peripheral Interface Connection (PlC) software. The programming about the motion of the robot has been built using the software developed. PicBASIC Pro-compiler and MicroCode studio from Microchip has been used to design a programming and compile the program. The PlC 18F4550 has been used as a microcontroller of the robot. The robot has a gripper at the top, in the middle and at the bottom of the robot's body which sequentially alternate between gripping and releasing the pole while moving upwards. Type HITEC HD7 150 M DC Servo Motor from Cytron Technologies Sdn. Bhd has been choose as a gear to move each pair of robot arms.